Containment : rebuilding a strategy against global terror - Shapiro, Ian (Princeton University Press, 2007)
In this powerfully argued book, Ian Shapiro shows that the idea of containment offers the best hope for protecting Americans and their democracy into the future. His bold vision for American security in the post-September 11 world is reminiscent of George Kennan's historic "Long Telegram," in which the containment strategy that won the Cold War was first developed. The Bush Doctrine of preemptive war and unilateral action has been marked by incompetence--missed opportunities to capture Osama bin Laden, failures of postwar planning for Iraq, and lack of an exit strategy. But Shapiro contends tha